Trends in Unintentional Injury Mortality Among Children and Adolescents in Poland, 2010–2024: An Unfinished Lesson for Public Health in Changing Social Realities - Rafał Halik; Mariusz Duplaga (Slovenian Journal of Public Health, 2026)
Abstract Introduction Unintentional injuries are a major cause of death among children and adolescents in Europe. Poland has historically reported elevated mortality levels. This study assesses national trends in injury mortality among individuals aged 1–19 years from 2010 to 2024. Methods A national time-trend analysis was conducted using Statistics Poland death registry data. Mortality rates were calculated by age group, sex, residence, and cause of death. Trends were modelled using log-linear Poisson regression to estimate annual percent change (APC). Global Burden of Disease estimates provided international context. Results A total of 6,812 deaths from unintentional injuries occurred during 2010–2024. Overall mortality decreased from 8.5 to 4.9 per 100,000 (APC −4.8%; 95% CI −5.3 to −4.3). The highest average mortality rate during 2010–2024 was observed in the 15–19 age group (15.4; 95% CI 14.9–15.8). Rural areas showed the steepest improvement (APC −6.7%), with rates declining from 11.7 in 2010 to 4.7 in 2024. The fastest age-specific decline occurred among children aged 5–9 years (APC −6.7%). Transport-related injuries contributed approximately 71% of the total decline. Drowning mortality showed the most pronounced relative decrease (APC −10.0%), while poisoning mortality increased significantly (APC +6.3%). Conclusions Mortality from unintentional injuries among children and adolescents in Poland has declined to levels comparable with the European Union; however, these improvements have been uneven across population groups. Further progress will require adapting prevention strategies to increasingly complex and evolving risk factors shaped by changing societal conditions.